Civilization aspects of the reflections on the direction of the change in the history of philosophy - Szumera, Grażyna (Folia Philosophica, 2003)
The topic of the present article is the historical and philosophical investigation into the source of civilisation and its course of development. The history of social thought is the history of the still unresolved disputes on whether the development of civilisation is intermittent or continuous, deterministic or voluntaristic. There are other similar problems such as: is the development of civilisation heading for a universal, unitary pattern? or is it pluralistic in its nature? is it governed by necessity or by accident? is it consonant with the universal laws of nature? or does it follow only its own laws? does it derive its creative energy from itself? or from some external factor? can it be evaluated as progressive? or is it just a development, a directional change, the evaluation of which is hazardous? It is impossible to present in the present article all the answers to the questions posed above, especially because, as far as the topics in question are concerned, it is hard to provide any unequivocal answers. Bearing this in mind, the author has been striving to avoid arbitrary judgements, presenting, instead, the arguments of selected thinkers on the problem of the development of civilisation. Because of the tensions and contradictions following in the wake of modern civilisation, these disputes do not die down but rather flare up. The thoughts of the selected philosophers are presented rather sketchily and in a simplified way, but the author feels that even so, a presentation of this kind will let the reader grasp the crucial importance of the problems that these thoughts touch upon, and will show the discussed thinkers as precursors of certain topical ideas.